Evaluating access: Comparing enrollment patterns in traditional versus multidisciplinary, project-based introductory statistics courses - Dierker, Lisa; Cooper, Jennifer; Selya, Arielle; Alexander, Jalen; Rose, Jennifer (Journal of Interdisciplinary Studies in Education, 2015)
To evaluate the potential impact of amultidisciplinary, project-based course on access to introductory statistics forunderrepresented students, this article examines differences in demographic anddisciplinary characteristics of students enrolling in a traditional introductorystatistics course compared to the multidisciplinary, project-based course.Administrative data were based on individual student enrollment from fallsemester 2009 and spring semester 2014. Results indicated that the project-basedcourse provided an increased number of seats and enrollment from a large rangeof majors. Higher rates of under-represented students chose the project-basedalternative over traditional introductory statistics. Though there was evidencethat the project-based course also attracted students with lower Mathachievement scores, a significant interaction between Math achievement andunder-represented student (URM) status demonstrated that URM studentsselecting the project-based course had lower math achievement scores than URMstudents selecting the traditional course suggesting that prior math achievement.